Analisis Komparatif Efektivitas Pahat Variable Helix Angle (VHA) dan Normal Helix Angle (NHA) untuk Pengendalian Regenerative Chatter pada Pemesinan CNC Milling Stainless Steel 304 - Venusa Abriandika; Ansor Salim Siregar; Agung Fauzi Hanafi; Indra Adi Saputra (Politeknik Negeri Banyuwangi, 2025)
This study compares the effectiveness of Variable Helix Angle (VHA) and Normal Helix Angle (NHA) end mills in controlling regenerative chatter during CNC milling of stainless steel 304. Experiments were conducted across a range of cutting parameters, including cutting speed, feed per tooth, and axial depth of cut, using VHA and NHA tools with identical basic geometries except for the helix angle. Measurements were obtained for vibration signals using an accelerometer, machined surface roughness (Ra), and tool wear. Signal analyses, including Fast Fourier Transform (FFT) and Power Spectral Density (PSD), experimental construction of stability lobe diagrams, and statistical evaluation using ANOVA, were employed to assess the influence of helix angle on stability limits and surface quality. The results are expected to determine whether VHA tools offer significant improvements in chatter suppression and expand the stable cutting region compared to NHA tools, as well as their implications for productivity and tool life when machining SS304. The findings provide practical recommendations for selecting cutter geometry in industrial applications where regenerative chatter poses a critical challenge.